Public Policy Strategies For Enhancing Innovation And SME Competitiveness In Emerging Economies - Bambang Wahrudin; Sutrisno (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
: In the landscape of emerging economies, the ability of small and medium enterprises (SMEs) to innovate and remain competitive plays a crucial role in promoting inclusive and sustainable economic development. This study investigates the role of public policy in enhancing SME innovation and competitiveness by employing a qualitative-descriptive method through library research. The analysis draws upon a diverse range of sources, including peer-reviewed academic journals, policy documents, and reports issued by international organizations such as the OECD, World Bank, and UNCTAD, published between 2005 and 2025. The findings underscore that well-structured policy frameworks, combined with targeted financial incentives, technology transfer mechanisms, and institutional support, significantly strengthen the innovation capabilities of SMEs. In addition, the presence of collaborative governance models particularly those involving public-private partnerships contributes to the development of robust innovation ecosystems. These ecosystems facilitate knowledge exchange, infrastructure sharing, and coordinated support among stakeholders. The study concludes that aligning innovation strategies with SME development objectives is essential for maximizing the role of SMEs in driving inclusive growth. As emerging economies seek to strengthen their innovation landscapes, tailored policy interventions, grounded in local contexts and supported by continuous evaluation, will be key to unlocking the transformative potential of SMEs in global value chains and national economies.